Adaptive expert knowledge / Nurmanisah Muhamed - Nurmanisah , Muhamed (2004)
Adaptive Expert Knowledge is a knowledge-based system. It consists of two modules which are the Expert Knowledge module and The On-going test module. Expert Knowledge module contains topics the student have to study. The topics are Speech, Vision and Motion of Robotic's domain. It is intelligent adaptive hypermedia where it will adapt according to the student's skills. During the study session, there will be an On-going test. Not all students can have access to the notes. There will be links to the notes. Links A is for student who is in Low level. Their marks for the Pretest is below 7. the notes for Link A is detailed and more examples than another two links. The purpose is so that the student will learn more about the topics and understand better. Link B is for Intennediate level students. The notes is lesser than the Link A. Students who are in Intennediate level can access Link A and Link B. The Intermediate level's mark is below 14 for the Pretest. Link C is for the High level students. Their knowledge about the Robotic domain is more than another two levels. Their marks for the Pretest is more than 13 marks of 20. The notes are simpler and mostly in point form. This is because they don't need to read notes that they already knew. The On-going test is the test which is inserted between the notes. The reason is to test the student's memory and help them to memorize better. Their marks will be calculated and display at the end of the learning session.